Analisis Pengaruh Roe, Tato, Der dan Size Terhadap Harga Saham Perusahaan: Studi Pada Emiten Sub Sektor Transportasi yang Terdaftar di BEI Periode 2013-2017 - Suryadarman Yusuf (Pusat Pengkajian dan Pengembangan Sumber Daya Manusia (P3SDM) Melati, 2020)
The purpose of this study was to analyze the effect of Return on Equity, Total Assets Turnover, Debt to Equity Ratio, and SIZE on Stock Price in transportation sub-sector companies listed on the Indonesia Stock Exchange for the period 2013-2017. The analysis method used is Data Panel Regression. The population in this study are all companies included in the transportation sub-sectors listed on the IDX for the period 2013-2017, as many as 35 companies. Determination of the number of samples was carried out using purposive sampling technique and determined by 24 companies. The results showed that TATO and DER had no effect on Stock Price. However, ROE and SIZE has a positive effect on Stock Price.